Implementation Of Thematic Agricultural Programs At The Department Of Food Crops, Horticulture, And Livestock, North Bengkulu - Desti Rohmatullah; Saputra, Harius Eko; Yusuarsono, Yusuarsono (Multidisciplinary Journals, 2025)
This study aims to analyze the implementation of thematic agricultural programs at the Department of Food Crops, Horticulture, and Livestock in North Bengkulu Regency. The program is part of a local government strategy to increase agricultural productivity, improve farmers’ welfare, and enhance local food security through training, technical assistance, and crop diversification. This research adopts a qualitative approach with data collected through observations, in-depth interviews, and documentation involving department staff and farmer groups participating in the program. The results indicate that program implementation involves active coordination between the department, field extension officers, and farmers. While communication and dissemination methods were relatively effective, challenges remain, particularly the limited number of agricultural extension workers and a lack of technical understanding among field actors. The program has been successful in enhancing farmers' knowledge, especially in sustainable practices and production efficiency. However, long-term sustainability requires regular evaluations, continuous training, and stronger policy support. Key factors influencing implementation success include effective communication, availability of human and financial resources, implementers' commitment, and supportive bureaucratic structures. By addressing these factors, the thematic agricultural program can serve as a participatory and sustainable development model for regional agricultural sectors.